CHOREA HYPERGLYCEMIA BASAL GANGLIA SYNDROME: A CASE REPORT OF A RARE DIABETES COMPLICATION - Nolasco, Remirr; Kingking, Neshreen; Dorado, Cristina; Fonte, Jay; Dadua-Ecal, Meliza (Journal of the ASEAN Federation of Endocrine Societies, 2022)
BACKGROUND Chorea hyperglycemia basal ganglia syndrome (C-H- BG) is a rare sequelae of acute hyperglycemia with a predilection for Asians and elderly women. Cases are often misdiagnosed with the more common intracerebral hemorrhage. The purpose of this report is to present this rare condition in a relatively young Asian male and discuss the approach to such cases. CASE A single case of C-H-BG was closely followed and recorded. A 53-year-old-male, Filipino, with type 2 diabetes mellitus and hypertension for more than 10 years, presented with sudden onset of hyperkinetic, involuntary, non-patterned, continuous movements of the left upper and lower extremities. Investigations revealed severe hyperglycemia (CBG 328 mg/dL; HbA1c 15.4%) without acidemia and ketonuria. Cranial computed tomography scan showed hyperdensity on the right caudate and lentiform nuclei. On cranial magnetic resonance imaging, there was T1-weighted hyperintense and T2-weighted hypointense signal involving the right putamen, globus pallidus and caudate. Cranial magnetic resonance angiography showed stenosis on the cavernous segment of the right internal carotid artery (ICA), left ICA and middle cerebral artery junction, the A1 segment of the left anterior communicating artery and proximal P2 segments of the bilateral posterior cerebral arteries. The patient was managed with a basal-bolus insulin regimen to control the blood glucose and haloperidol to manage the extrapyramidal symptoms. Consequently, there was complete resolution of the involuntary movements. CONCLUSION This case emphasizes the importance of early recognition of this rare diabetes complication. Manifestations of C-H-BG are debilitating but reversible through aggressive glucose control and haloperidol.